SIGNIFIKANSI KEPERCAYAAN SUAMI ISTRI DALAM MEMBENTUK KEHARMONISAN KELUARGA PADA PASANGAN MUDA MUSLIM (Studi Desa Batu Putih Kecamatan Sekotong Kab. Lombok Barat) - Setiawati, Sulis; Abdullah (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2023)
This research examines in depth two things, namely first, strategies for building trust between husband and wife in forming family harmony among young Muslim couples and second, the problems faced by husband and wife in building trust to form family harmony among young Muslim couples in Batu Putih Village, Sekotong District, Regency. West Lombok. The research method used in this research is a qualitative method, this research was carried out in Batu Putih village, West Sekotong District. The data collection methods used were observation methods, interview methods and documentation methods. The results of this research show that the Strategy for Building Trust between Husband and Wife in Forming Family Harmony in Young Muslim Couples in Batu Putih Village can be done in four ways, namely instilling honesty in the household, and the second is by instilling the nature of mutual trust in a household. respect and be wise in solving problems. There are three main underlying problems faced by husband and wife in building trust to form family harmony among young Muslim couples in Batu Putih Village, namely: poor communication relationships, the average economic condition of the community is low. and the Rights and Obligations of the Wife Ignored by the Husband.